2020
DOI: 10.1002/rcs.2150
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve analysis of robotic transabdominal preperitoneal inguinal hernia repair

Abstract: Background: The purpose of this study was to assess the learning curve (LC) for inguinal hernia repair with robotic transabdominal preperitoneal (R-TAPP) approach. Methods: Between April 2016 and October 2019, patients who underwent R-TAPP were retrieved. Patient demographics, operative variables and postoperative outcomes were assessed. The moving average method and cumulative sum of operation times (OT) were used to evaluate the LC. The surgeon (BB) in this study had completed his laparoscopic (Lap) TAPP exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Our evaluation of the LC of a simple surgical technique excluded the effects of differences, such as surgical team performance or docking the da Vinci robotic system, other than operative or console time. Reports of completed LC for R‐TAPP by expert surgeons in L‐TAPP varied from 25 to 139 cases, but the majority of studies reported 30–50 cases, similar to our results 13–18 . We also performed 50 cases of RG during the same period.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our evaluation of the LC of a simple surgical technique excluded the effects of differences, such as surgical team performance or docking the da Vinci robotic system, other than operative or console time. Reports of completed LC for R‐TAPP by expert surgeons in L‐TAPP varied from 25 to 139 cases, but the majority of studies reported 30–50 cases, similar to our results 13–18 . We also performed 50 cases of RG during the same period.…”
Section: Discussionsupporting
confidence: 83%
“…However, considering the widespread use of the DVSS and other systems, we believe that our results are more realistic because surgeons adopting robotic surgery in their practices are likely to incorporate this approach in several types of procedures. LC for R‐TAPP for surgeons performing robotic surgery for other diseases within the study period have been reported 13,14 . For example, Aghayeva et al 13 reported that performing robotic surgery for other diseases may lead to a crossover effect that shortens the operation time for R‐TAPP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a series of their initial RAWS cases ( 8 ) acknowledge a significant decrease of OT in the second half of the first 25 bilateral rTAPP operations performed by an experienced senior surgeon ( trainee type B ). ( 9 ) found that for a senior surgeon experienced in both laparoscopic hernia repair and robotic gastrointestinal surgery ( trainee type C ) 35 cases seemed to be needed to achieve optimum OT for rTAPP. Ebeling et al ( 10 ) described a dedicated training program for residents ( trainee type X ) for rTAPP of groin hernias.…”
Section: The Learning Curve For Robot Assisted Abdominal Wall Surgery...mentioning
confidence: 99%